Differences in the head movement during baseball batting between skilled players and novices - Nakata, H.; Miura, A.; Yoshie, M.; Kudo, K. (The Journal of Strength and Conditioning Research, 2012)
We investigated the pattern of head movement during baseball batting in 8 skilled players and 9 unskilled novices, using a high-speed video camera. The 2 directions of head movement were analyzed as an X-axis (from the home plate to the pitcher's plate) and Z-axis (vertical downward). On the X-axis, peak latency, peak value, the distance from the peak to the value at bat-ball impact, and data variability were compared between the 2 groups. On the Z-axis, peak latency, downward distance, and data variability were analyzed. Peak latency on the X-axis occurred significantly earlier in baseball players than in novices (p < 0.001), and the difference between the minimum peak and impact was significantly larger in the players (p < 0.05). The variability in peak latency on the X-axis was significantly larger in the novices (p < 0.05). The variability in peak value on the Z-axis was also significantly larger in the novices (p < 0.05). Our findings showed that the significant differences in head movement between the 2 groups should help baseball players, beginners, coaches, and strength and conditioning professionals to improve performance, be effectively applied to actual practice, and enhance coaching for batting.